Organizational Culture, OCB, Motivation, and Support in Lecturer Performance - Rusul, Ahmad Khitamur; Sudiro , Achmad; Amanah Jiwa Juwita, Himmiyatul (Jurnal Ilmiah Administrasi Publik, 2026)
This study examines the influence of organizational culture on lecturer performance by integrating Organizational Citizenship Behavior (OCB) and work motivation as mediating variables and Perceived Organizational Support (POS) as a moderating variable. Grounded in (Robbins, S., & Judge, 2017) Organizational Behavior framework, this research seeks to explain how cultural values within higher education institutions shape lecturers’ attitudes, motivation, and discretionary behaviors, which in turn affect their performance. Data were collected from 241 lecturers at Nahdlatul Ulama University Surabaya (UNUSA) through online and offline surveys and analyzed using the Partial Least Squares (PLS) method. The findings indicate that organizational culture significantly enhances OCB and work motivation but does not directly influence lecturer performance. Both OCB and work motivation act as mediating mechanisms that translate cultural values into performance outcomes, while POS strengthens these indirect relationships. This study contributes to the organizational behavior literature by providing empirical evidence on how culture, motivation, and citizenship behavior interact to improve lecturer performance, offering practical implications for enhancing institutional effectiveness and competitiveness among private universities in Indonesia.